Some Bessel type additive inequalities in inner product spaces - DRAGOMIR, Silvestru Sever (Studia Universitatis Babeș-Bolyai Mathematica, 2021)
In this paper we obtain some additive inequalities related to the cele- brated Bessel’s inequality in inner product spaces. They complement the results obtained by Boas-Bellman, Bombieri, Selberg and Heilbronn, which have been applied for almost orthogonal series and in Number Theory. Mathematics Subject Classification (2010): 46C05, 26D15.